Guilt as a Motivator for Moral Judgment: An Autobiographical Memory Study - Knez, Igor; Nordhall, Ola (Frontiers in Psychology, 2017)
The aim was to investigate the phenomenology of self-defining moral memory and its relations to self-conscious feelings of guilt and willingness to do wrong (moral intention) in social and economic moral situations. We found that people use guilt as a moral motivator for their moral intention. The reparative function of guilt varied, however, with type of situation; that is, participants felt guiltier and were less willing to do wrong in economic compared to social moral situations. The self-defining moral memory was shown to be relatively more easy to access (accessibility), logically structured (coherence), vivid, seen from the first-person perspective (visual perspective), real (sensory detail); but was relatively less positive (valence), emotionally intense, chronologically clear (time perspective), in agreement with the present self (distancing), and shared. Finally, it was indicated that the more guilt people felt the more hidden/denied (less accessible), but more real (more sensory details), the self-defining moral memory.